Modeling stochastic anomalies in an SIS system. Issue 1 (2nd January 2017) - Vlasic, Andrew; Day, Troy
ABSTRACT: We propose a stochastic SIS model to include both a Gaussian and Poissonian perturbation to account for noise and anomalies in the transmission rate. Conditions are given for stability to the disease free equilibrium and for positive Harris recurrence with a unique invariant measure for the endemic.